2023
DOI: 10.1021/acssuschemeng.3c00655
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Transformation and Characterizations of Super-deamidated Wheat Gluten by a Tunable Hydrated Ternary Natural Deep Eutectic Solvent

Abstract: The utilization of natural deep eutectic solvents (NADESs) for super-deamidation of wheat gluten represents a costeffective approach to expand its potential applications as a plant protein source and reduce the occurrence of allergens. However, NADESs are susceptible to deconstruction during hydration, leading to unstable super-deamidation. Herein, we prepared a ternary hydrated NADES (HB 3 C 1 G 1 -N) composed of betaine, citric acid, and glucose, doubling the protein preparation concentration (50 mg/mL) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In light of these observations, it is evident that further exploration into the tunability of NADES and the application of advanced optimization methodologies could signi cantly contribute to the re nement and enhancement of ultrasound-assisted extraction processes. Such advancements not only promise to elevate the e ciency and sustainability of extracting valuable phytochemicals from plant materials but also offer a pathway One study revealed that the TFC yield was twice as high when using green technology and green solvents [ 47 ]. In a study of DESs prepared with citric acid:malic acid:water (1:1:10), the TFC values of the persimmon pulp were determined, and the value was calculated as 2.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these observations, it is evident that further exploration into the tunability of NADES and the application of advanced optimization methodologies could signi cantly contribute to the re nement and enhancement of ultrasound-assisted extraction processes. Such advancements not only promise to elevate the e ciency and sustainability of extracting valuable phytochemicals from plant materials but also offer a pathway One study revealed that the TFC yield was twice as high when using green technology and green solvents [ 47 ]. In a study of DESs prepared with citric acid:malic acid:water (1:1:10), the TFC values of the persimmon pulp were determined, and the value was calculated as 2.…”
Section: Discussionmentioning
confidence: 99%